Analysis Of The Influence Of Price Perception, Value Perception And Quality Perception On Intention To Repurchase Samsung Electronic Products - Elizabeth Elizabeth; Sulistyo Budi Utomo; Ngurah Pandji Mertha Agung Durya; I Wayan Gede Antok Setiawan Jodi; Dedik Wiryawan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The impact of perceived price, perceived quality, and perceived value on the desire to repurchase Internet of Things items is examined in this study. A sample of 100 respondents who utilize Samsung Android phones as part of the Internet of Things is used in this study’s primary data. Multiple linear regression tests are run on the data before processing. According to the study’s findings, perceived price has no appreciable impact on consumers’ intentions to buy Internet of Things items again. The propensity to repurchase Internet of Things items is strongly influenced by perceptions of quality.The propensity to repurchase Internet of Things items is strongly influenced by perceptions of value. The desire to repurchase Internet of Things devices is significantly influenced by perceived price, perceived quality, and perceived value all at once.